“Are you going to wear a dress now?”: Nonhegemonic Masculinities in Ocean Vuong’s On Earth We’re Briefly Gorgeous - Inês Santos (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
This article analyses the work of Ocean Vuong, specifically his engagement with queerness and its impact on individuals. In On Earth We’re Briefly Gorgeous, Vuong constructs a world marked by both beauty and pain, centered on the transformative relationship between Little Dog and Trevor. Drawing on the theoretical contributions of sociologist Raewyn Connell, as well as the ongoing debate within the interdisciplinary field of Masculinities, I demonstrate how Vuong articulates multiple forms of masculinity and how, ultimately, Little Dog and Trevor—characters who embody nonhegemonic masculinities—endure the violence imposed by those surrounding them. This research deepens the critical understanding of this contemporary novel and situates it within a broader scholarly context; through a close reading of the masculinities embedded in the narrative, we can discern how queer and feminist studies are inevitably intertwined with masculinity and the societal pressures that compel men to perform constructed alter egos. In a novel defined by grief, cultural displacement, and numerous structural and interpersonal obstacles, the persona into which Little Dog is coerced reflects the broader social forces shaping his existence. In a world populated by men who imagine themselves as natural-born leaders aligned with hegemonic ideals—ordained to rule, dominate, marry, and reproduce—the narrative foregrounds those who exist on the margins of hegemonic masculinity and asserts the necessity of recognising their experiences.